Effect of a Luteinizing Hormone Releasing Hormone Agonist Given During Combination Chemotherapy on Posttherapy Fertility in Male Patients With Lymphoma: Preliminary Observations - Johnson, David H.; Linde, Randy; Hainsworth, John D.; Vale, Wylie; Rivier, Jean; Stein, Richard; Flexner, John; Welch, R. Van; Greco, F. Anthony (Blood, 1985)
Six men undergoing potentially curative chemotherapy for advanced lymphomas received daily injections (50 μg) of an analogue of luteinizing hormone releasing hormone (LH-RHa) in an attempt to protect posttreatment gonadal function. The median duration of combined LH-RHa-chemotherapy administration was 25 weeks (range, 14 to 31 weeks). During the simultaneous administration of LH-RHa and chemotherapy, plasma testosterone levels decreased to subnormal levels, while both follicle-stimulating hormone (FSH) and luteinizing hormone levels declined to the lower limit of normal. All subjects became oligospermic or azoospermic within eight weeks of starting treatment. Following discontinuation of chemotherapy and LH-RHa, both plasma testosterone and LH promptly increased and stabilized within the normal range. FSH progressively increased to a level well above the normal range. Only one patient has recovered evidence of active spermatogenesis at 84 weeks postcessation of chemotherapy. No untoward side effects due to LH-RHa were experienced. Although LH-RHa can be administered safely during combination chemotherapy, no improvement in posttreatment fertility has yet been demonstrated.